Habitat Suitability Model of Some Important Large Mammals In The Western Black Sea Region - UGIŞ, Abdullah; AKKUZU, Erol; Evcin, Özkan (Springer Science and Business Media LLC, 2024)
Abstract
The Western Black Sea region in Türkiye harbors diverse ecosystems that support a variety of wildlife, including several important large mammal species. Understanding the habitat suitability of these species is crucial for effective conservation and management strategies. In this study large mammal species existing in Kastamonu Balldağ and Kurtgirmez located Western Black Sea region were determined by using the camera trap method. Brown bear (Ursus arctos), jackal (Canis aureus), roe deer (Capreolus capreolus), red deer (Cervus elaphus), wolf (Canis lupus), marten (Martes sp.), badger (Meles meles), otter (Lutra lutra), fox (Vulpes vulpes), lynx (Lynx lynx), wild boar (Sus scrofa), wild cat (Felis silvestris) and Brown hare (Lepus europeaus) were identified. Habitat suitability models were created for Canis lupus, Capreolus capreolus and Ursus arctos mammal species using MaxEnt (Maximum Entropy) modeling approach. Presence data of target species were collected through field surveys, to create habitat suitibility models with environmental variables such as slope, aspect, ruggedness index, elevation, topographic position index, solar radiation index, landform, road density, settlement areas, and forest condition. The MaxEnt models were trained using these data to predict habitat suitability across the region. Our results reveal spatial patterns of habitat suitability for each species, highlighting areas of high suitability that may serve as priority conservation areas. Furthermore, we discuss the implications of our findings for conservation planning and management efforts in the Western Black Sea region, emphasizing the importance of integrating habitat suitability models into decision-making processes to ensure the long-term persistence of these important mammal species.